MicroSweat: A Wearable Microfluidic Patch for Noninvasive and Reliable Sweat Collection Enables Human Stress Monitoring. Issue 7 (3rd December 2022) - Shajari, Shaghayegh; Salahandish, Razieh; Zare, Azam; Hassani, Mohsen; Moossavi, Shirin; Munro, Emily; Rashid, Ruba; Rosenegger, David; Bains, Jaideep S.; Sanati Nezhad, Amir
Abstract: Stress affects cognition, behavior, and physiology, leading to lasting physical and mental illness. The ability to detect and measure stress, however, is poor. Increased circulating cortisol during stress is mirrored by cortisol release from sweat glands, providing an opportunity to use it as an external biomarker for monitoring internal emotional state. Despite the attempts at using wearable sensors for monitoring sweat cortisol, there is a lack of reliable wearable sweat collection devices that preserve the concentration and integrity of sweat biomolecules corresponding to stress levels. Here, a flexible, self‐powered, evaporation‐free, bubble‐free, surfactant‐free, and scalable capillary microfluidic device, MicroSweat, is fabricated to reliably collect human sweat from different body locations. Cortisol levels are detected corresponding to severe stress ranging from 25 to 125 ng mL −1 averaged across multiple body regions and 100–1000 ng mL −1 from the axilla. A positive nonlinear correlation exists between cortisol concentration and stress levels quantified using the perceived stress scale (PSS). Moreover, owing to the sweat variation in response to environmental effects and physiological differences, the longitudinal and personalized profile of sweat cortisol is acquired, for the first time, for various body locations. The obtained sweat cortisol data is crucial for analyzing human stress in personalized and clinical healthcare sectors. Abstract : This paper presents a flexible, self‐powered, skin‐interfaced, surfactant‐free microfluidic patch (MicroSweat) for reliable sweat collection and Chrono sampling of sweat from different body locations and chemical analysis of sweat cortisol stress biomarker. MicroSweat facilitates the potential benefit of measuring stress levels using the cortisol concentrations of the armpit sweat. It also signifies personalizing sweat cortisol for longitudinal and daily effects.